(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Communicative Language Teaching, as a responsive teaching approach to the needs of learners, has been extensively recognized as a favorable approach to EFL teachers and learners around the world. The main purpose of this study is to investigate the attitudes of EFL students towards CLT in an Afghan EFL setting. It also attempts to determine the effects of CLT activities on their motivation and CLT challenges by their demographic profile. The data were collected from 201 English major undergraduate students from the Faculty of Language and Literature at Takhar University purposefully through a questionnaire which consists of 30 items. For answering the research questions, descriptive statistics, sample T-test, and a one-way ANOVA test were employed. The findings revealed that Afghan EFL students have positive attitudes towards CLT approach. The study also showed that the attitude of the students towards CLT is positive in terms of their gender. Moreover, there is no statistically significant difference among the group factors (age, first language, and English learning experience) of the participants.